Overweight and Obesity in Schoolchildren: Hierarchical Analysis of Associated Demographic, Behavioral, and Biological Factors - Cézane P. Reuter; Elza D. de Mello; Priscila T. da Silva; Tássia S. Borges; Elisa I. Klinger; Silvia I. R. Franke; Andréia R. de M. Valim (Hindawi Limited, 2018)
Studies focused on the mechanisms involved in the development of obesity in children and adolescents have reported associations between this condition and birth weight, sedentary lifestyle, and hereditary conditions. However, few studies have simultaneously evaluated these factors. This cross-sectional study aims to identify demographic, behavioral, and biological factors associated with overweight/obesity in children and adolescents. 381 schoolchildren aged seven to 17 years were included in the study to evaluate the associations between overweight/obesity and biological factors (including family history of obesity, birth weight, and the fat mass and obesity-associated (FTO) rs9939609 polymorphism), demographic variables (including gender and age), and behavioral variables (including physical activity and/or sports participation). The results of this study showed that there was a lower prevalence of obesity in schoolchildren aged 11-17 years (PR: 0.89; p=0.004). Obesity was more prevalent in children whose father (PR: 1.24; p<0.001) and maternal grandmother (PR: 1.16; p=0.019) were obese. Higher prevalence rates of obesity were also identified in schoolchildren who were overweight at birth (PR: 1.18; p=0.002) and carriers of the obesity risk genotype (PR: 1.13; p=0.016). Biological factors, such as family history of obesity, overweight at birth, and the presence of the fat mass and obesity-associated rs9939609 polymorphism were associated with the prevalence of obesity in children and adolescents.